Cancer care continuity: A qualitative study on the experiences of French healthcare professionals, patients and family caregivers. (June 2019) - Lelorain, Sophie; Moreaux, Clémence; Christophe, Véronique; Weingertner, Françoise; Bricout, Hélène
Introduction: Continuity of care has many positive outcomes. Yet, in oncology, it may rapidly be disrupted. It is therefore essential to investigate the perceptions of users. Our aim was thus to describe and compare the perceptions of cancer care continuity of patients, family caregivers and various healthcare professionals involved in cancer care in France, one of the countries most affected by cancer. Methods: The urology and senology cancer departments of two hospitals, as well as community physicians, were involved: 54 hospital healthcare professionals including mainly physicians, nurses and medical secretaries; 12 city physicians; 41 patients and their family caregivers. We carried out a qualitative study using N-Vivo® and a deductive approach to code the interviews into the following dimensions of continuity: informational, organisational and relational. Results: Three different perspectives were highlighted: hospital healthcare professionals primarily focused on organisational aspects (71% of their discourse), city physicians on their need for information from hospitals (40% of their discourse) and patients/caregivers on relational aspects with professionals (51% of their discourse). However, the three dimensions of continuity were intertwined, as the major focus of each type of participant impacted their perspective of the other spheres of coordination. Discussion: Working on the main perspective of each category of person involved in cancer care could improve, in turn, the other spheres of continuity for these people. For example, dealing with organisational issues with hospital physicians could be an indirect and original way to enhance their relationships with patients, which are so important to the latter.